Surface applied lime dynamics and base saturation index in a consolidated no-tillage area - Bortolini, Diego; Cassol, Luís César; Piva, Jonatas Thiago; Bosi, Cristiam; Rocha, Kassiano Felipe [UNESP] (Lepidus Tecnologia, 2016)
The aim of this study was to evaluate the behavior of chemical properties and crop yields during five years after liming, in a consolidated no-tillage system area and indicate a base saturation index to serve as a criterion for recommendation. The experiment was conducted in a randomized complete block design with four repetitions, being the treatments the five lime doses (0, 2.4, 4.8, 7.2 and 9.6 Mg ha-1) applied and maintained on the soil surface. Soil chemical properties were evaluated in eight soil sampling, in the layers 0 to 0.025; 0.025 to 0.05; 0.05 to 0.10; 0.10 to 0.15; 0.15 to 0.20 and 0.20 to 0.40 m, besides crop grain yield (wheat, soybean and corn) and black oat dry matter yield, totaling five years of evaluation. The surface liming in no-tillage system increased the exchangeable magnesium and calcium contents, base saturation and soil pH and reduced the exchangeable aluminum content. The cumulative grain yield (six crops) and black oat dry matter yield (three crops) was not influenced by liming. These results suggested, from this study conditions, that the value of 50% of base saturation should be adopted as a criterion for liming for crops implanted under consolidated no-tillage systems.
Keywords: Aluminium; Chemical characteristics; Liming; Liming recommendation